Media Video Pembelajaran Interaktif Berbasis Problem Based Learning Pada Mata Pelajaran IPAS - I Dewa Ngakan Made Widnyana Artha; Anak Agung Gede Agung; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2024)
This research is motivated by students who use more textbooks, but the number is limited. Students quickly get bored because there is no variation in learning media. The purpose of this study is to analyze interactive learning videos based on problem-based learning in science learning for grade IV elementary school. The method used in the development is ADDIE. The ADDIE method is a systematic method consisting of 5 main stages, namely analysis, design, development, implementation, and evaluation. This study uses data collection methods in the form of questionnaires and tests. The data analysis technique used is a quantitative descriptive and inferential statistical analysis of the t-test. The results of this study are the design of interactive learning videos from the analysis stage to the evaluation stage, the validity of the experts, the practicality based on individual, small group, and field tests, and the effectiveness of interactive learning videos based on problem-based learning seen from the calculation of the t-test show that there is a significant difference in learning outcomes before and after using interactive learning videos based on problem-based learning. The post-test value is above the KKTP; it is concluded that the use of interactive learning videos based on problem-based learning is effective in improving learning outcomes for grade IV. The implications of this research can improve analytical thinking and problem-solving skills that are useful outside the academic context.